Penyelesaian Sengketa Proses Pendaftaran Tanah Sistematis Lengkap (PTSL) Berdasarkan Peraturan Menteri Agraria Nomor 6 Tahun 2018 - I Gusti Ayu Agung Kosalya; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Fakultas Hukum Universitas Warmadewa, 2022)
Land registration which aims to provide legal certainty is known as Rechts Cadaster / Legal Cadastre. The guarantee of legal certainty to be realized in this land registration includes the certainty of the rights registered. The formulation of the problem in this study is: how is the strength of physical and juridical data on the process of registering land rights in light of the Guideline of the Priest of Agrarian Undertakings and Spatial Preparation of the Republic of Indonesia Number 6 of 2018 concerning Total Methodical Land Enlistment (PTSL) and how is the settlement interaction for land freedoms questions in view of the Guideline of the regulation of Agrarian Issues and Spatial Preparation of the Republic of Indonesia Number 6 of 2018 concerning Total Orderly Land Enrollment (PTSL). The strength of physical and juridical data on the process of registering land rights in Gianyar Regency from regulation of Agrarian Issues and Spatial Preparation of the Republic of Indonesia Number 6 of 2018 The process of resolving on a plot of land for dispute resolution which is resolved through non-litigation channels by calling the two parties concerned to the BPN office for deliberation or mediation.